2015
DOI: 10.1088/0004-637x/808/1/75
|View full text |Cite
|
Sign up to set email alerts
|

KINEMATICS OF THE X-SHAPED MILKY WAY BULGE: EXPECTATIONS FROM A SELF-CONSISTENTN-BODY MODEL

Abstract: We explore the kinematics (both the radial velocity and the proper motion) of the vertical X-shaped feature in the Milky Way with an N-body bar/bulge model. From the solar perspective, the distance distribution of particles is double-peaked in fields passing through the X-shape. The separation and amplitude ratio between the two peaks qualitatively match the observed trends towards the Galactic bulge. We confirm clear signatures of cylindrical rotation in the pattern of mean radial velocity across the bar/bulg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…The 'bulge bar' rows refer to the orbital speed at the end of the short thick bar (set at a radius of 2.1 kpc [8]) straddling the stellar bulge, while various published models [86,87] found it an angular velocity value (column 4), from which equation 6 here yielded its orbital speed at this radius (velocity in column 6), while equation 7 yielded an orbital period (column 8).…”
Section: Angular Rotation and Orbitsmentioning
confidence: 99%
“…The 'bulge bar' rows refer to the orbital speed at the end of the short thick bar (set at a radius of 2.1 kpc [8]) straddling the stellar bulge, while various published models [86,87] found it an angular velocity value (column 4), from which equation 6 here yielded its orbital speed at this radius (velocity in column 6), while equation 7 yielded an orbital period (column 8).…”
Section: Angular Rotation and Orbitsmentioning
confidence: 99%
“…Shen et al (2010); Li & Shen (2012); Ness et al (2013b) showed that the observed X-shape and cylindrical rotation could be reproduced with an N-body B/P Bulge model. Gardner et al (2014); Qin et al (2015) explained the different kinematics of stars on the near and far parts of the X in the Bulge. Portail et al (2015b); Williams et al (2016); Abbott et al (2017) showed that the B/P Bulge is maintained by a wide range of orbits, both resonant and non-resonant.…”
Section: Bulge Dynamics and Massmentioning
confidence: 99%
“…This is because a bar is preferentially supported by prograde orbits. As Qin et al (2015) showed, simply using the rotational velocity at a few spatial locations to estimate the pattern speed leads to biases. The geometric factors and averaging in the estimators are a necessary component.…”
Section: The Pattern Speed Of the Barmentioning
confidence: 99%